STUDENTS IN REGARDING FORMS IN CLASS XI IPA 1 SMA NEGERI 1 BUA PONRANG DISTRICT LUWU - Indah Wahyuni Syamsu Wahyuni Syamsu; Abd Aziz Ahmad; Pangeran Paita Yunus (Universitas Negeri makassar, 2019)
This study aims to determine the ability of students to draw a form in class XI IPA 1 SMA Negeri 1 Bua Ponrang Luwu. The research design used is descriptive evaluation design. The purpose of this study is to determine the ability of students in drawing the form in class XI IPA 1 SMA Negeri 1 Bua Ponrang. The benefits of research can provide input for the school in an effort to develop the potential of resources possessed by students in drawing the form and can provide an overview to students to determine the techniques in drawing the form. The population in this study were 173 people for five classes and the sample was 32 people. Data collection techniques used observation techniques, interviews, documentation, practice tests. Based on the results of the research can be concluded that: The ability of students to draw a form in class XI IPA 1 SMA Negeri 1 Bua Ponrang Luwu regency classified in sufficient category. The average value of the overall results obtained from the perspective, composition, proportion and darkness of the appraiser 1 by Mr. Sidik Mustajab shows that 8 students are capable, 15 students are quite capable, and 9 students show less able. And from Assessor 2 by Mr. Muh. Amir shows students' results from the perspective, composition, proportion and dark aspects that only one student and 10 can afford and 21 less students. And from the results of the appraisal value 3 by the father Prince Paita Yunus just give value on the proportion only. Students of SMA Negeri 1 Bua Ponrang Luwu Regency classified show thoroughly on the results of drawing the form of the KKM value of 65.